EFEK PENSTABIL OKSIGEN SINGLET EKSTRAK PEWARNA DARI DAUN BAYAM TERHADAP FOTOOKSIDASI ASAM LINOLEAT, PROTEIN DAN VITAMIN C - Katja, Dewa (Sam Ratulangi University, 2009)
The objective of this research was to determine singlet oxygen quenching (SOQ) effects of colorantextracts of spinach leave on erythrosine-sensitized photooxidation of linoleic acid, protein and vitamine C.Spinach leave was extracted with water, ethanol 40%, 60% and 80% for 30 minutes. Analyses ofantioxidant phytochemicals were based on total phenolic and flavonoid contents. The extracts of spinachleaf evaluated singlet oxygen quenching effect using linoleic acid, protein and vitamine C as substrates eachcontaining 5 ppm erythrosine was exposed under fluorescent light (4000 lux). Extraction with ethanol 40%showed the highest yield of extract, followed with ethanol 60%, water and ethanol 80%. The result showedthat solvent was significantly have an effect on total phenolic content, which ethanol 60% extract was thehighest, followed with 80 and 40% ethanol extracts and water extract. Contrary, ethanol 40%, extractpossessed highest total flavonoid content than water extract, ethanol 60% and ethanol 80% extract.Futhermore, the result determined SOQ, water extract possessed highest SOQ compared with ethanol40%, 60% and 80% in photooxidation of linoleic acid system. However, ethanol extract 40% and ethanolextract 60% showed that highest activity than ethanol extract 80% and water extract in photoxidation ofprotein system whereas in photooxidation of vitamin C system, ethanol extract 60% showed higest activitycompared with etnanol extract 80, ethanol extract 40% and water. It is concluded that colorant extract ofspinach leave showing singlet oxygen quenching effect was a component having phenolic groupÂ Keywords : color, phenolic extract, spinach leaves, singlet oxygen quenching